KESEPADANAN TERJEMAHAN TINDAK TUTUR TIDAK LANGSUNG DALAM NOVEL SHERLOCK HOLMES KARYA SIR ARTHUR CONAN DOYLE - Fitriani, Nurul (Jurnal Sasindo UNPAM, 2017)
AbstractThe purpose of this study is to obtain an overall view of translation equivalence of indirect speech acts from English to Bahasa Indonesia. This study used a qualitative approach using a content analysis method. The data used in this study is dialogues about indirect speech acts found in Sherlock Holmes novel written by Sir Arthur Conan Doyle. Findings of this study are as follows: First, the translation of indirect speech acts found are as many as 136 data. Second, the translation equivalences used are formal equivalence and dynamic equivalence. There are 47 data classified into formal equivalence, while the rest, 89 data are classified into dynamic equivalence.Keywords: Sherlock Holmes, equivalence, translation, indirect speech acts.